EFEKTIVITAS PELAKSANAAN PROGRAM SISTEM KELAS TUNTAS BERKELANJUTAN (SKTB) DI SMP NEGERI 1 TOMPOBULU KABUPATEN GOWA - Fitriani Fitriani; Imam Suyitno; Dr. Mustaring, M.Hum (Jurnal Tomalebbi, 2019)
Abstract; This article addresses the issue of the Effectiveness of the Implementation of the Sustainable Completed Classroom System (SKTB) in SMP Negeri 1 Tompobulu. This research is a qualitative descriptive study, the primary data source is the informant consisting of school principals, eleven subject teachers and ten students. Secondary data are school data documents. Data collection techniques through interviews, observation and documentation. The results showed that (1) The implementation of the automatic promotion system in SMP Negeri 1 Tompubulu was carried out by (a) Allowing students to complete and incomplete to graduate (b) Complete all students before graduating. This causes no more students in SMP Negeri 1 Tompobulu to stay in class, therefore there are students who cannot read even though they are sitting in class IX. (2) The implementation of early clinics in SMP Negeri 1 Tompobulu is only given through written tests and special assignments at the end of the semester, providing short re-learning, while providing special guidance is only given to students who cannot read. (3) Enrichment is carried out by way of being billed or not billed, and is given based on material by some teachers in SMP Negeri 1 Tompobulu and some other teachers do not provide enrichment. Based on the three indicators, the implementation of the Sustainable Completed Class Program in SMP Negeri 1 Tompobulu has not been effective because the plan / program has not been implemented as a whole, so the tasks and objectives of the Sustainable Completed Class System (SKTB) have not been achieved.Keywords: Effectiveness, Implementation, SKTB Program